Form-based postponement in the solid hardwood supply network - Sebastian Kühle; Alfred Teischinger; Manfred Gronalt (Cogent Business & Management, 2019)
For the foreseeable future the hardwood production network has an advantage due to the increasing availability of resources. The main challenge is to integrate the upcoming volume of raw material into the existing supply chain for sustainable value creation. This paper examines a form-based postponement concept in order to understand the balance between the benefits of increasing flexibility and the costs caused by it. The contribution of this paper is to apply a form postponement concept in the forest- and wood-based sector, especially the hardwood sector. This paper contains a process flow chart with additional production processes, parameters for material yields of the alternative production processes, an optimization model which calculates the lowest supply network cost and a case study with several network configurations. Results computed from the developed model and configurations show that there are several potentials for an enhanced flexibility of the supply network. On the one hand the combined processes lead to a higher material yield and on the other hand the specification of the product can be carried out later in production. This is made possible by the modularity of the products, by finishing processes at the end of the production unite and by the identification of more decoupling points.
Keywords: 650; Postponement; supply network; beech wood; hardwood laminated wood product; flexibility; process flow; decoupling point